2022
DOI: 10.3389/fpubh.2022.1002466
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia among patients with type 2 diabetes in Jordan: Prevalence, pattern, and associated factors

Abstract: ObjectivesTo determine the prevalence and patterns of dyslipidemia and its associated risk factors among patients with type 2 diabetes attending the National Center for Diabetes, Endocrinology, and Genetics (NCDEG).MethodsA cross-sectional study was conducted at the NCDEG in Amman, Jordan. A total of 971 patients with type 2 diabetes were included during the period September- December 2021. The socio-demographic data were collected through face-to-face interview questionnaire and anthropometric and clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The majority of participants 51% (122) had a duration of disease of fewer than six years and among them 75% (91) had dyslipidemia. Similar results were observed by Hyassat et al [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of participants 51% (122) had a duration of disease of fewer than six years and among them 75% (91) had dyslipidemia. Similar results were observed by Hyassat et al [12].…”
Section: Discussionsupporting
confidence: 92%
“…Borle et al discovered that 28% (14) of participants exhibited isolated lipid profile abnormalities, while 58% (29) had combined and mixed lipid profile abnormalities [8]. According to Hyassat et al, 62.48% (493) of participants had combined and mixed deranged lipid profiles and 27.8% (220) had isolated lipid profile abnormality [12]. A study by Sarfraz et al also observed that 34% (68) participants had isolated and 66% (132) had combined and mixed dyslipidemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…The dyslipidemic triad was defined as the simultaneous presence of elevated TG, reduced HDL-C, and increased levels of low-dens LDL-C. In the Jordanian population, it was evident from multiple cohort studies that advanced age, hypertension, smoking status, poor lipid profile, obesity, DM, and others are major risk factors for developing ASCVDs [ 13 , 14 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Unlike the results of this study, other research revealed that the age of type 2 diabetic patients was significantly linked with elevated LDL-C and hypertriglyceridemia. 21 The difference may be due to the study populations. Thus, extensive research would unknot the paradox.…”
Section: Correlation Between High-density Lipoprotein and Blood Glucosementioning
confidence: 99%
“…These findings agree with those reported in several other studies providing further evidence that in poor glycemic control, the likelihood of a high concentration of LDL-C would be increased. 20,21,39 Therefore, blood glucose could be utilized to predict the level of LDL-C in diabetic patients because blood glucose can cause the defect of LDL which leads to the formation of plaque inside the artery.…”
Section: Association Of Blood Glucose and Ldl-c Concentrationsmentioning
confidence: 99%